What contributes to consumer price inflation? A novel decomposition framework with an application to Austria - Martin Schneider (Oesterreichische Nationalbank (OeNB), 2024)
In this paper, we propose a new methodology for decomposing consumer price inflation into contributions of cost components using national accounts data. It builds on the well-known decomposition method for the value-added deflator and expands it by combining the cost structure of the consumption bundle underlying the harmonized index of consumer prices (HICP) derived from an input-output table with quarterly national accounts data. This allows to decompose HICP inflation into detailed cost components including imports. We apply the approach to Austria and analyze the composition of inflation for the period from the first quarter of 2019 to the first quarter of 2023. In 2022, the most significant contributors to inflation were both energy and non-energy imports. Profits contributed to inflation from the second half of 2022 onwards, whilst there have been no substantial price pressures from wages. We also find that there are considerable differences in the inflation determinants between subindices of the HICP. Whilst imports played a crucial role for inflation of food, non-energy industrial goods and energy, their influence for services inflation was minimal. The results of the analysis show that the decomposition can provide valuable insights for the conduct of monetary policy.
Keywords: C67; E25; E31; 330; Consumer price inflation; production-side decomposition; inflation accounting